The Power of Scientometrics and the Development of Economics - Jakob Kapeller; Matthias Aistleitner; Stefan Steinerberger (Johannes Kepler University Linz, Institute for Comprehensive Analysis of the Economy (ICAE), 2016)
Citation metrics and its related indices and rankings become increasingly important in the evaluation of research. Such indices are part of a more general tendency aiming for the simplification of complex and interconnected phenomena through quantification. The purpose of our contribution is to analyze the impact of such quantitative indices on the further development of science with a special emphasis on economics. In this case we observe a multitude of interesting effects on both, the level of individual scientists as well as the global development of the discipline.
Keywords: A14; B50; 330; pluralism; academic reproduction; paradigms; citation metrics; reactivity; quantification